1978
DOI: 10.1002/pol.1978.170161118
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifier‐free emulsion polymerization of tetrafluoroethylene by radiation. I. Effects of reaction conditions on the polymerization rate and polymer molecular weight

Abstract: The radiation‐induced emulsifier‐free emulsion polymerization of tetrafluoroethylene was carried out at an initial pressure of 2–25 kg/cm2, temperature of 30–110°C, and under a dose rate of 0.57 × 104−3.0 × 104 rad/hr. The rate of polymerization was shown to be proportional to 1.0 and 1.3 powers of the dose rate and initial pressure, respectively, and is maximal at about 70°C. The molecular weight of polytetrafluoroethylene (PTFE) lies in the range of 105−106, increases with reaction time in the early stage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
3

Year Published

1979
1979
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
4
3
Order By: Relevance
“…This means that the higher temperature can cause a higher degree of coagulation. This behavior is different from that found in Suwa et al18 results; in that study, emulsion polymerization of TFE by radiation showed that the rate increases with the rising reaction temperature (70°C) and then decreases. Consequently, it is shown as the behavior of the typical radical polymerization.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…This means that the higher temperature can cause a higher degree of coagulation. This behavior is different from that found in Suwa et al18 results; in that study, emulsion polymerization of TFE by radiation showed that the rate increases with the rising reaction temperature (70°C) and then decreases. Consequently, it is shown as the behavior of the typical radical polymerization.…”
Section: Resultscontrasting
confidence: 84%
“…The apparent activation energy obtained by a slope of a plot of ln R p vs. 1/ T of Figure 16 is −0.7 kcal/mol, between 55 to 95°C. This value is lower than that obtained by Suwa et al (−5.2 kcal/mol),18 compared to the range of negative dependence of 1/ T for the rate of polymerization. This difference may be due to the initiator or agitation speed.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…27 This behavior may be related to the decomposition rate of initiators like APS. This behavior is different from that found in Suwa et al 18 results; in that study, emulsion polymerization of TFE by radiation showed that the rate increases with the rising reaction temperature (70°C) and then decreases. 33 Therefore, the particles formed rapidly in the nucleation period may be unstable, and hence, easy to coagulate; the surface area of the particles is large, and there is not enough surfactant to cover the nucleated particles.…”
Section: Effects Of Reaction Temperature (T)contrasting
confidence: 81%
“…Randomly arranged anisotropic rodlike features have been observed in thin films formed from bulk PTFE latexes . Both spherical and rodlike particles have been observed from conventional emulsion polymerization of TFE to form PTFE. , Studies of the formation of PTFE dispersion particles have revealed distinct nucleation and growth periods during polymerization. ,, Although the transition from the nucleation to the growth period depends on process conditions, in several cases, it has been found to occur within the first few minutes of polymerization, whether it be in an emulsion polymerization with a surfactant 21 or in an emulsifier-free radiation-induced emulsion polymerization . As growth proceeds, PTFE chains adapt a helical conformation that is highly linear, directional, and rigid with no branching or cross-linking. , Further, the development of highly extended PTFE chains favor the formation of rodlike grains because, through electron microscopy and X-ray diffraction, rodlike PTFE particles consist of extended chains aligned in the direction of the long axis of the rods. , Thus, a polymerization process that provides less nucleation would allow greater subsequent growth from these sites and would favor more extended chains with less chain ends and more rodlike grains.…”
Section: Resultsmentioning
confidence: 99%